(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
This investigation aimed to prepare Cilnidipine Nanoparticles by nanoprecipitation ultrasonication method and to study the significance of processing variables by applying quality by design. Cilnidipine is fourth-generation dual L/N-type Ca2+ channel blocker used for the management of hypertension. It is BCS class-II drug exhibiting lower aqueous solubility, which tends to lower bioavailability. The combination of Poloxamer 188 and Tween 80 was used as a stabilizer. The design of the experiment is one of the tools of Quality by design. Plackett -Burman design was applied for the screening of processing variables, which are significant for the method. The processing variables screened were stirring speed, antisolvent ratio, drug concentration, polymer concentration, stabilizer concentration. The effect of each parameter evaluated by particle size, entrapment efficiency, and drug release at 10 minutes of prepared Nanoparticles of Cilnidipine. Analysis of variance and Pareto-plot of Plackett-Burman design were utilized to find the significance of the factor and extent of the effect. The surface morphology of Cilnidipine Nanoparticles was studied by SEM. The Pareto plot, as well as statistical analysis of design, had shown that the Concentration of drug, solvent: antisolvent ratio and concentration of poloxamer 188 were the significant parameters for the method. The stabilizer concentration, the stirring speed, and the antisolvent ratio had a negative effect of while the concentration of drug has a positive effect on the particle size of Nanoparticles and drug release at 10 minutes and positive effect of entrapment efficiency of Cilnidipine Nanoparticles. The Cilnidipine Nanoparticles were characterized by FTIR and DSC analysis.